CORPORATE CRIMINAL LIABILITY: AN ANALYSIS OF CORPORATE CRIME PERPETRATORS UNDER POSITIVE LAW IN INDONESIA - Widyaningrum, Tuti; Khoirunnisa, Khoirunnisa; Jubaidi, Didi (LPPM STIH Putri Maharaja, 2024)
This research discusses corporate criminal liability in Indonesia regarding corporate crime perpetrators in positive law. The economic interdependence between nations has increased the need for legal rules related to international trade and business. Corporate crimes have significant negative impacts on society and the environment. This research aims to analyze how corporate criminal liability is established based on positive laws in Indonesia regarding corporate crime perpetrators. This research employs a normative juridical approach, utilizing literature studies encompassing various sources such as books, online media, dissertations, and other relevant literature. The discussion encompasses the concept of corporate accountability in criminal acts and debates about who can be held accountable, the corporate entity or its executives. The results of this research serve as a basis for evaluating and improving the existing legal framework and contribute to developing more effective policies in addressing corporate crimes in Indonesia. The regulations regarding criminal liability for corporate crime perpetrators in Indonesia currently lack clear provisions and are scattered across multiple legislations. Therefore, a new Criminal Code should be promptly enacted to avoid legal loopholes in enforcing corporate criminal acts.